The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1007/s11906-019-0994-z
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Safeguards Cardiorenal and Metabolic Diseases: a Protective Role in Health

Abstract: Purpose of Review-To discuss recent advances indicating that bilirubin safeguards against cardiorenal and metabolic diseases. Recent Findings-Several investigations from human patient populations and experimental animal models have shown that bilirubin improves cardiorenal and metabolic dysfunction. The latest studies found an entirely new function of bilirubin suggesting that it acts as a hormone signaling molecule capable of activating nuclear receptors for burning fat, which may explain several of its prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 60 publications
2
27
0
2
Order By: Relevance
“…Others have shown that the bilirubin nanoparticles protect against hepatic ischemia-reperfusion injury (Kim et al, 2017a), inflammatory lung disease (Kim D. E. et al, 2017), colitis and gut microbiome (Lee et al, 2019), and pancreatic islet xenotransplantation (Kim M. J. et al, 2017). There is promise in bilirubin nanoparticles as a therapeutic, and bilirubin is protective of the cardiovascular system (Hinds and Stec, 2018;Hinds and Stec, 2019) by improving blood pressure (Vera et al, 2009) and renal blood flow (Vera and Stec, 2010). Total bilirubin serum levels were negatively associated with cerebral atherosclerosis, and higher levels had less incidence of extracranial arterial stenosis (ECAS) and intracranial arterial stenosis (ICAS) (Kim et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have shown that the bilirubin nanoparticles protect against hepatic ischemia-reperfusion injury (Kim et al, 2017a), inflammatory lung disease (Kim D. E. et al, 2017), colitis and gut microbiome (Lee et al, 2019), and pancreatic islet xenotransplantation (Kim M. J. et al, 2017). There is promise in bilirubin nanoparticles as a therapeutic, and bilirubin is protective of the cardiovascular system (Hinds and Stec, 2018;Hinds and Stec, 2019) by improving blood pressure (Vera et al, 2009) and renal blood flow (Vera and Stec, 2010). Total bilirubin serum levels were negatively associated with cerebral atherosclerosis, and higher levels had less incidence of extracranial arterial stenosis (ECAS) and intracranial arterial stenosis (ICAS) (Kim et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that the heme metabolite, bilirubin, reduce fat accumulation and blood glucose levels in obese mice (Dong et al, 2014;Hinds et al, 2014;Liu et al, 2015;Gordon et al, 2016;Stec et al, 2016;Hinds et al, 2017;Takei et al, 2019;Stec et al, 2020). Bilirubin offers a promising therapeutic approach as it benefits the cardiovascular system (Hinds and Stec, 2018;Hinds and Stec, 2019) by preventing hypertension (Vera et al, 2009) and improving blood flow (Vera and Stec, 2010). Bilirubin's actions to reduce lipid accumulation have been attributed to the recent findings that it has a hormonal function by binding directly to the nuclear receptor peroxisome proliferator-activated receptor α (PPARα), which induces gene transcription that promotes fat burning (Gordon et al, 2016;Stec et al, 2016;.…”
Section: Introductionmentioning
confidence: 97%
“…This was mostly reflected from the severe hyperbilirubinemia observed in the extremely rare Crigler–Najjar syndrome with levels in the 400–700 μM range, which can cause brain damage in infants [ 44 ]. The past two decades of heme oxygenase and bilirubin research has shown that bilirubin has many health benefits [ 1 , 2 , 45 ]. For instance, humans with the UGT1A1*28 Gilbert’s polymorphism that causes reduced levels of the UGT1A1 enzyme and increased plasma bilirubin levels in the 18–50 μM range [ 46 , 47 ], have been shown to have decreased incidence of cardiovascular disease [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise and diet modifications are beneficial in reducing body weight and adverse outcomes. Recent investigations have shown that bilirubin, which was typically considered a toxic bile substance, has beneficial actions on regulating body weight [1,2]. Indeed, there has been a correlation showing that plasma bilirubin levels are lower in obese humans [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In animal models of myocardial ischemia (MI), both overexpression and pharmacological induction of HO-1 reduce infarct size and ventricular remodeling after ischemia-reperfusion damage by improving cardiac metabolism [ 143 ]. Increased HO-1 expression has a protective effect against ischemia-reperfusion injury in the kidney [ 144 ] and can correct blood pressure elevation following ang-II exposure [ 145 ].…”
Section: Cardiorenal Syndrome and Ho-1mentioning
confidence: 99%